IN MEMORIAM - Prof. Heinz Langer - Borogovac, Muhamed (Sarajevo Journal of Mathematics, 2025)
We are deeply saddened by the passing of Professor Emeritus Dr. rer. nat. Heinz Langer, who left us on January 25, 2024, in Bern, at the age of 89. Born on August 8, 1935, in Dresden, Prof. Langer had a distinguished career in mathematics, primarily at TU Dresden and, from 1991 to 2003, at TU Wien. Heinz Langer was among the leading mathematicians in Functional Analysis of his generation. His work was driven by a pure dedication to mathematical research: solving problems and exploring mathematical mysteries. He once remarked, ”If your results are good, people will make the effort to read them, wherever they are published.” Though he paid little attention to metrics like citation counts or journal prestige, his contributions are impressive: over 200 publications, approximately 3,000 citations, numerous collaborators and doctoral students, and multiple awards and recognitions from around the world.